Comparison of Apical Root Resorption encountered during Maxillary Incisor retraction using Stainless Steel Boot Loop and TMA Boot Loop – A Case Series - Gupta, Gaurav; Singh, Raj Kumar; Relhan, Ashima; Singh, Gurkeerat; Goyal, Abhishek (Orthodontic Journal of Nepal, 2016)
External apical root resorption (EARR) is probably the most common iatrogenic sequel of orthodontic treatment. The present case series focuses on the incisor retraction using frictionless mechanics. Boot loop made up of .019x.025 Stainless steel or TMA archwire were used for maxillary incisor retraction. Retraction with stainless steel boot loop showed greater root resorption as compared to TMA boot loop. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.45-48